LuxS quorum sensing system and biofilm formation of oral microflora: A short review article - Abdurahman A. Niazy (Saudi Dental Journal)
The LuxS quorum sensing system is considered as the main system that most of the oral bacteria use to communicate in order to create biofilms. Here we identified 11 of the most important biofilm formers that utilize the LuxS system and presented current and recent information regarding this system. Though different bacterial species are able to communicate thorough the LuxS system, it was also found that cross kingdom communication can occur between bacteria and fungi and bacteria and epithelial cells. Immune response also plays and important role in mitigating the effects of biofilms. Here we identified 6 of the most important molecules that are involved in the immune response to biofilms. These immune molecules maintain the stability in the oral cavity by preventing bacteria from overwhelming the space and simultaneously minimizing the immune response in order not to cause tissue damage. Here we also discuss current research being done in order to maintain the balance in the oral cavity via inhibiting biofilm formation without eradicating oral bacteria in order to prevent the overgrowth of other organisms such as Candida albicans. One approach being used is inhibiting AI-2 intermediates which leads to lack of quorum sensing communication between bacteria through the use of intermediate analogues. Another approach that found success is the utilization of D forms of sugars where D-ribose and D-galactose have been proven to inhibit the LuxS system and subsequently preventing the process of quorum sensing leading to the reduction in biofilm formation.